PELESTARIAN LINGKUNGAN DENGAN PENURUNAN LAJU EROSI MELALUI KEGIATAN PENANAMAN DAN PEMELIHARAAN POHON REBOISASI - Zakaria, Fauzan; Gafur, Mahyunita Abdul; Nurmi, Nurmi (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2024)
The purpose of community service is to preserve the environment by reducing the rate of erosion through planting and maintaining reforestation trees around Tunggulo reservoir which is located in a sloping topography area. The method used in this community service is to conduct counseling on the benefits of fruit trees (soursop, rambutan, and durian) in increasing the cover of vegetation canopy on the soil surface so that it can reduce the rate of soil erosion, in addition to providing economic value to the community. The results of the community service are in the form of transferring research results on reforestation tree planting and maintenance technology, in this case tree planting with weed removal only carried out around trees planted in the direction of the contour lines. Partners play an active role in this community service, especially in the technical implementation in the field. The community service program carried out was accepted by farmers. Farmers are very optimistic that they can apply what they have learned in this community service activity in the field, because this technology is very easy to apply. Planting is carried out together with local residents and maintenance is continued by students during the implementation of the KKN program. Of the three types of fruit trees planted, soursop plants have better growth compared to rambutan and durian plants